Genetic Diversity Study in Sorghum Using Quantitative Morphological Traits - Sinha, Sweta; Kumaravadivel, N. (International Journal of Bio-resource and Stress Management, 2023)
Assessment of genetic diversity and identification of superior genotypes are important prerequisites for a successful crop improvement program. In the present investigation, 40 sorghum accessions consisting of sweet sorghum, grain sorghum, forage sorghum, mutant lines, maintainer lines and restorer lines, were screened for genetic diversity using quantitative traits. Observations were recorded on 14 quantitative traits, out of which 9 diverse traits contributing to maximum variability were selected for genetic diversity analysis. The principle component analysis revealed that the panicle width, stem girth and leaf breadth, contributed maximum towards divergence. By using hierarchical cluster analysis, the 40 accessions were grouped under 6 clusters. Cluster I contained maximum number of accessions and cluster VI contained the minimum. The maximum inter cluster distance was observed between cluster VI and cluster IV. Cluster III had the highest mean value for hundred seed weight and yield. Hence the accessions falling under these clusters could be used as the parents for hybridization programme in sorghum. Thus, morphological data were able to reveal the existence of a wide genetic diversity among the sorghum accessions used providing scope for further genetic improvement.